QUR’ANIC INTERPRETATION ON INSTAGRAM: The Shift from Traditional to Digital Platforms in Indonesia - Rasidin, Rasidin; Nurfadliyati, Nurfadliyati; M Syam, Masiyan; Taufik, Taufik; Ilham, Muhammad (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
This article examines the shifting landscape of Qur’anic interpretation in Indonesia, from traditional platforms to digital spaces, by focusing on contemporary practices emerging on social media, particularly Instagram. Employing netnografi, the study investigates the activities of two Instagram accounts, @yufid.tv and @quranreview, over a five-month period (January–May 2022). Of the 300 posts by yufid.tv, 20.67% featured interpretations of specific Qur’anic verses. Meanwhile, 74.36% of the 39 interpretive posts by @quranreview addressed contemporary social issues and trends. The findings reveal a significant transformation in the mode of Qur’anic interpretation in the digital era, from unidirectional, text-heavy delivery characteristic of traditional methods to more interactive, visually driven approaches. The concept of dakwahtainment, a fusion of dakwah and entertainment, has become a defining feature of Instagram-based interpretations. Rather than merely presenting textual exegesis, these accounts repackage Qur’anic messages using light packaging, headline appetite, and trailer vision, making the content more engaging and accessible. In this context, Instagram functions as a new public space where Qur’anic interpretation intersects with Islamic pop culture, fostering a communicative, adaptive, and socially responsive form of digital dakwah.